Idea for business - Mohd Sam, Mohd Fazli; Mohamed, Nurul Hasyimah; Nizam, Nurul Zarirah; Hashim, Nik Mohd Zarifie (Penerbit UTeM Press, 2023)
This module is a reference guidebook for Idea for Business subjects in higher learning institutions. It consists of ten chapters, including the introduction of The Entrepreneurial Myth Revisited & Orientation, entrepreneurship foundation theories, start-up business in Malaysia, venture formation, successful business concepts, components of a complete business model, developing a business concept, mind map, and business model, and marketing and growth strategies. The module is written in simple language and includes questions at the end of each chapter to help students understand the subject matter. The authors express gratitude to the university for their support and gratitude to friends and colleagues for their friendly inspiration and help.